A Practicioner's Guide to Evaluating the Impacts of Labor Market Programs - Fitzsimons, Emla; Vera-Hernandez, Marcos (World Bank, Washington, DC, 2012)
This note provides an introduction to the impact evaluation of labor market programs, with particular reference to developing countries. Its focus is on the main issues that need to be considered when planning an impact evaluation, including the importance of rigorous design for an evaluation, and on the statistical techniques used to estimate program impacts. To help the exposition, a prototype of a training program is referred to intermittently throughout the note. This hypothetical training program, which authors call get-to-work, provides training to the unemployed to help them find work. The note describes some general issues that are important for any impact evaluation of employment programs, both in the design and analysis stages, regardless of the specific evaluation techniques used. It then describes the main evaluation techniques, including the data requirements and the main assumptions invoked by each.